Graduates of UMP, the preferred choice of the job market - UMP, PNC (2019)
The engineering and technology programmes offered by Universti Malaysia Pahang (UMP) have always undergone advancement and given added values through continuous benchmarking process using world-class model, a result of a partnership programme with Karlsruhe University of Applied Science (HsKA) Germany.